Lessons from the COVID-19 pandemic for improving outpatient neuropalliative care: A qualitative study of patient and caregiver perspectives. (July 2021) - Macchi, Zachary A; Ayele, Roman; Dini, Megan; Lamira, Jensine; Katz, Maya; Pantilat, Steven Z; Jones, Jacqueline; Kluger, Benzi M
Background: COVID-19 has impacted persons with serious illness, including those with chronic, neurodegenerative conditions. While there are several reports on COVID-19's impact on inpatient palliative care, literature is limited about the impact on outpatient care which may be more relevant for these patients. Aim: To generate a person-centered description of the impact of COVID-19 from the perspectives of patients living with neurodegenerative disease and caregivers to improve outpatient palliative care delivery. Design: This qualitative study used rapid analysis via matrix design to identify emergent themes related to participant perspectives on the challenges of COVID-19. Data sources included semi-structured interviews, open-ended survey responses, medical record documentation and participant-researcher communications. Setting/Participants: Data was collected from 108 patients with Parkinson's disease, Alzheimer's disease or related disorders and 90 caregivers enrolled in a multicenter, clinical trial of community-based, outpatient palliative care between March 20, 2020 and August 8, 2020 (NCT03076671). Results: Four main themes emerged: (1) disruptions to delivery of healthcare and other supportive services; (2) increased symptomatic and psychosocial needs; (3) increased caregiver burden; (4) limitations of telecommunications when compared to in-person contact. We observed that these themes interacted and intersected. Conclusions: Patients and caregivers have unmet care needs because of the pandemic, exacerbated by social isolation. While telemedicine has helped improve access to healthcare, patients and caregivers perceive clear limitations compared to in-person services. Changes in society and healthcare delivery in response to COVID-19 highlight ongoing and novel gaps that must be addressed to optimize future outpatient palliative care for neurologic illness.